Are quadratics that easy?

Algebra Level 3

Consider all pairs of non-zero integers ( a , b ) (a,b) such that the equation

( a x b ) 2 + ( b x a ) 2 = x ( ax-b)^2 + (bx-a)^2 = x

has at least one integer solution.

The sum of all (distinct) values of x x which satisfy the above condition can be written as m n \frac{ m}{n} , where m m and n n are coprime positive integers. What is the value of m + n m + n ?


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Hugh Sir
Sep 24, 2014

The given quadratic equation can be rewritten as ( a 2 + b 2 ) x 2 ( 4 a b + 1 ) x + ( a 2 + b 2 ) = 0 (a^{2}+b^{2})x^{2}-(4ab+1)x+(a^{2}+b^{2}) = 0 Since one of the roots is an integer, the two roots are real numbers.

So the discriminant of the quadratic is non-negative. ( 4 a b + 1 ) 2 4 ( a 2 + b 2 ) 2 0 (4ab+1)^{2}-4(a^{2}+b^{2})^{2} \ge 0 ( 1 + 2 ( a + b ) 2 ) ( 1 2 ( a b ) 2 ) 0 (1+2(a+b)^{2})(1-2(a-b)^{2}) \ge 0 Since the first factor ( 1 + 2 ( a + b ) 2 ) (1+2(a+b)^{2}) is always positive, the second factor must be non-negative. 1 2 ( a b ) 2 0 1-2(a-b)^{2} \ge 0 ( a b ) 2 1 2 (a-b)^{2} \le \frac{1}{2} Since a a and b b are non-zero integers, the value of ( a b ) (a-b) must be zero.

Thus, a = b a = b

Then the given quadratic can be written as 2 a 2 x 2 ( 4 a 2 + 1 ) x + 2 a 2 = 0 2a^{2}x^{2}-(4a^{2}+1)x+2a^{2} = 0

Suppose the roots of the quadratic are x 1 x_{1} and x 2 x_{2} ; where x 1 x_{1} is the integer root.

By Vieta's formula, x 1 x 2 = 1 x_{1}x_{2} = 1 x 1 + x 2 = 2 + 1 2 a 2 x_{1}+x_{2} = 2+\frac{1}{2a^{2}}

Note that x 1 0 x_{1} \ne 0 and x 1 1 x_{1} \ne 1 . So x 1 2 x_{1} \ge 2 x 2 = 1 x 1 > 0 x_{2} = \frac{1}{x_{1}} > 0 2 x 1 < x 1 + x 2 2 \le x_{1} < x_{1}+x_{2} As a a is a non-zero integer, thus a 2 1 a^{2} \ge 1 x 1 + x 2 = 2 + 1 2 a 2 2.5 x_{1}+x_{2} = 2+\frac{1}{2a^{2}} \le 2.5 2 x 1 < x 1 + x 2 2.5 2 \le x_{1} < x_{1}+x_{2} \le 2.5 As x 1 x_{1} is an integer, so x 1 = 2 x_{1} = 2 and x 2 = 1 2 x_{2} = \frac{1}{2}

The sum of the roots is 2 + 1 2 = 5 2 = m n 2+\frac{1}{2} = \frac{5}{2} = \frac{m}{n} m + n = 5 + 2 = 7. m+n = 5+2 = 7.\square

That's exactly how it is done! Great solution!!!

Jordi Bosch - 6 years, 8 months ago

This is a really elegant solution to a beautiful problem.. love it!! :D

Aritra Jana - 6 years, 8 months ago

hey plz explain how D>0 or D=0 when one of the root is integer.

muhmd sani - 6 years, 5 months ago
Rohit Sachdeva
Sep 27, 2014

The quadratic equation becomes:

( a 2 + b 2 ) x 2 ( 4 a b + 1 ) x + ( a 2 + b 2 ) = 0 (a^{2}+b^{2})x^{2}-(4ab+1)x+(a^{2}+b^{2})=0

Since one root is integer, hence Discriminant,

D = B 2 4 A C 0 D=B^{2}-4AC ≥0

( 1 + 4 a b ) 2 ( 2 ( a 2 + b 2 ) ) 2 0 (1+4ab)^{2}-(2(a^{2}+b^{2}))^{2}≥0

( 1 + 2 ( a + b ) 2 ) ( 1 2 ( a b ) 2 ) 0 (1+2(a+b)^{2})(1-2(a-b)^{2})≥0

Since first bracket is always +ve, the second bracket needs to be ≥0

1 2 ( a b ) 2 0 1-2(a-b)^{2}≥0

( a b ) 2 1 / 2 (a-b)^{2}≤1/2

Since a & b are non-zero integers, hence,

( a b ) 2 = 0 (a-b)^{2}=0 or a = b a=b

Now, let roots of given quadratic be x 1 x_{1} (integer) and x 2 x_{2}

Sum of roots = -B/A and Product of roots = C/A

x 1 + x 2 = ( 4 a . a + 1 ) / ( a 2 + a 2 ) = 2 + 1 / 2 a 2 x_{1}+x_{2}= (4a.a+1)/(a^{2}+a^{2})=2+1/2a^{2}

x 1 x 2 = 1 x_{1}x_{2}=1 or x 2 = 1 / x 1 x_{2}=1/ x_{1}

x 1 + 1 / x 1 = 2 + 1 / 2 a 2 x_{1}+1/x_{1}=2+1/2a^{2}

Since a is non-zero integer, a 2 1 a^{2} ≥1

2 + 1 / 2 a 2 2 + 1 / 2 = 2.5 2+1/2a^{2}≤2+1/2=2.5

2 x 1 + 1 / x 1 2.5 2 ≤ x_{1}+1/x_{1}≤2.5

Hence,

x 1 = 2 x_{1}=2 and x 2 = 1 / 2 x_{2}=1/2

x 1 + x 2 = 5 / 2 = m / n x_{1}+x_{2}=5/2=m/n

m + n = 7 m+n=7

Nicely done!

Jordi Bosch - 6 years, 8 months ago

Please explain why the minimum value of x1 + x2=2.

Raven Herd - 6 years, 4 months ago
Joel Tan
Oct 13, 2014

Let me attempt a proof with inequalities.

Lemma. For all reals m , n , m 2 + n 2 0.5 ( m + n ) 2 m, n, m^{2}+n^{2} \geq 0.5(m+n)^{2} This is a result of Cauchy Schwarz inequality.

Let m = a x b , n = b x a m=ax-b, n=bx-a so x 0.5 ( a + b ) 2 ( x 1 ) 2 x \geq 0.5(a+b)^{2}(x-1)^{2} and thus ( a + b ) 2 2 x ( x 1 ) 2 (a+b)^{2} \leq \frac {2x}{(x-1)^{2}} . We let 2 x ( x 1 ) 2 \frac {2x}{(x-1)^{2}} be y y .

Consider y y . If x > 3 , y < 1 x> 3, y <1 so a + b < 1 a = b a+b<1 \implies a=-b . Substituting, 2 a 2 ( x + 1 ) 2 = x 2 ( x + 1 ) 2 2a^{2}(x+1)^{2}=x \geq 2 (x+1)^{2} , contradiction. Hence x = 1 , 2 , 3 x=1, 2, 3 . (x is positive) But 3 cannot be written as the sum of two perfect squares, so we consider 1 and 2.

x = 1 2 ( a b ) 2 = 1 x=1 \implies 2 (a-b)^{2}=1 which is a contradiction.

x = 2 ( 2 a b ) 2 + ( 2 b a ) 2 = 2 x=2 \implies (2a-b)^{2}+(2b-a)^{2}=2 . This gives ( 2 a b ) 2 = ( 2 b a ) 2 = 1 (2a-b)^{2}=(2b-a)^{2}=1 . WLOG let a b a \geq b . This gives the solutions ( a , b ) = ( 1 , 1 ) , ( 1 3 , 1 3 ) , ( 1 , 1 ) (a, b)=(1, 1), (\frac {1}{3}, -\frac {1}{3}), (-1, -1) . Note that ( 1 , 1 ) , ( 1 , 1 ) (1, 1), (1, -1) give the same x. So we just need to consider ( 1 , 1 ) (1, 1)

The equation is now 2 ( x 1 ) 2 = x 2 (x-1)^{2}=x which has two solutions 2 and 0.5. Hence their sum is 5 2 \frac {5}{2} and the answer is 7.

Yatiraj Tantri
Sep 24, 2014

On rearranging ( a x b ) 2 + ( b x a ) 2 = x (ax-b)^{2} + (bx-a)^{2} = x we get ( a 2 + b 2 ) x 2 ( 4 a b + 1 ) x + ( a 2 + b 2 ) = 0 (a^{2}+b^{2})x^{2} - (4ab+1)x + (a^{2}+b^{2}) = 0

The roots of the above equation are: ( ( 4 a b + 1 ) + / ( ( 4 a b + 1 ) 2 4 ( a 2 + b 2 ) 2 ) ) / ( 2 ( a 2 + b 2 ) ((4ab+1) +/- \sqrt((4ab+1)^{2} - 4(a^{2}+b^{2})^2)) / (2(a^{2}+b^{2})

It's given that x has an integer solution. So we can eliminate the complex solutions. That means to say, ( 4 a b + 1 ) 2 > 4 ( ( a 2 + b 2 ) ) 2 (4ab+1)^{2} > 4((a^{2} + b^{2}))^{2} i.e. ( 4 a b + 1 ) 2 > ( 2 ( a 2 + b 2 ) ) 2 (4ab+1)^{2} > (2(a^{2} + b^{2}))^{2}

It's given that a and b are non-zero integers. By giving various values for a and b in the above inequality, we see that the inequality is satisfied only when a = b.

With a=1, b=1, we get x = 2 or 1/2.

Sum of roots of x is 2+(1/2) = 5/2.

5 and 2 are co-prime (which is one of the conditions for the solution: m/n, m and n are co-prime)

m+n = 5+2 = 7.

You should say why the inequality is satified only when a=b.

Jordi Bosch - 6 years, 8 months ago
Carsten Meyer
Feb 24, 2019

First we notice the left hand side is a non-negative real, so x 0 x\geq0 . By trial and error we find one possible solution and show that x ∉ { 0 ; 1 } x\not\in\{0;\:1\} : ( a 1 ; b 1 ; x 1 ) = ( 1 ; 1 ; 2 ) , x = 0 : a 2 + b 2 0 , x = 1 : 2 ( a b ) 2 1 m o d 2 \begin{aligned} (a_1;\:b_1;\:x_1)&=(1;\:1;\:2),&&&&&x&=0:&a^2+b^2&\neq 0,&&&&&x&=1:&2(a-b)^2&\neq 1\mod 2 \end{aligned} Now to the general case. We expand the equation and may divide by a 2 + b 2 2 a^2+b^2\geq 2 , because a , b 0 a,\:b\neq0 : 0 = x 2 4 a b + 1 a 2 + b 2 x + 1 = : x 2 2 k x + 1 x 1 , 2 = k ± k 2 1 ( ) \begin{aligned} 0&=x^2-\frac{4ab +1}{a^2+b^2} x +1=:x^2-2kx+1&&&\Rightarrow &&&&x_{1,2}&=k\pm\sqrt{k^2-1} & (*) \end{aligned} To get (at least) one non-negative real solution, we need k 1 k\geq 1 . Using AM-GM-HM (arithmetic/geometric/harmonic mean inequality) on k k : k 4 a b + 1 2 ( a 2 + b 2 ) = 1 1 2 ( a b + b a ) + 1 2 ( a 2 + b 2 ) HM-GM 1 + 1 2 2 = 5 4 a 2 + b 2 2 \begin{aligned} |k|\leq\frac{4|ab|+1}{2(a^2+b^2)}&=\frac{1}{ \frac{1}{2}\left(\frac{|a|}{|b|}+\frac{|b|}{|a|}\right) } + \frac{1}{2(a^2+b^2)}\underset{\text{HM-GM}}{\leq} 1+\frac{1}{2\cdot 2}=\frac{5}{4} &&&\left| a^2+b^2\geq 2\right. \end{aligned} With the remaining values for k k , try to get an upper estimate for the solutions: k [ 1 ; 5 4 ] : x 1 , 2 = k ± k 2 1 k + k 2 1 5 4 + 25 16 1 = 2 \begin{aligned} k&\in \left[1;\:\frac{5}{4}\right]: &&& |x_{1,2}|&=|k\pm\sqrt{k^2-1}|\leq |k|+\sqrt{k^2-1}\leq\frac{5}{4}+\sqrt{\frac{25}{16}-1}=2 \end{aligned} The only possible non-negative integer solutions are x { 0 ; 1 ; 2 } x\in\{0;\:1;\:2\} . We already eliminated the first two and showed that x 1 = 2 x_1=2 is indeed a solution to the problem. Vieta's Formula in ( ) (*) yields the second root x 2 = 1 2 x_2=\frac{1}{2} , so x 1 + x 2 = 5 2 = m n x_1+x_2=\frac{5}{2}=\frac{m}{n} , and the answer is m + n = 7 m+n=\boxed{7}

Lu Chee Ket
Oct 16, 2014

x^2 - 2 [(2 ab + 0.5)/(a^2 + b^2)] x + 1 = 0

x = (2 ab + 0.5)/(a^2 + b^2) +/- SQRT{[(2 ab + 0.5)/(a^2 + b^2)]^2 - 1}

Discriminant >= 0

=> [(2 ab + 0.5)/(a^2 + b^2)]^2 - 1 >= 0

=> [(2 ab + 0.5)/(a^2 + b^2) + 1][(2 ab + 0.5)/(a^2 + b^2) - 1] >= 0

=> [(2 ab + 0.5)/(a^2 + b^2) - 1] >= 0

=> 0.5 >= a^2 + b^2 - 2 a b

=> (a - b)^2 <= 0.5

Only integer sets allowed are a - b = 0 where a = b such as (a, a). (a, -a) is also eliminated.

x = (1 + 0.25/ a^2) +/- SQRT[(1 + 0.25/ a^2)^2 - 1]

Discriminant = (0.25/ a^2)(2 + 0.25/ a^2) must always satisfy greater than or equal to zero.

(1 + 0.25/ a^2) - SQRT[(1 + 0.25/ a^2)^2 - 1] is not likely an integer. With a = 1 to 20 and a = -1 to -20 for examples [Where only non-zero (a, a) is wanted],

x = (1 + 0.25/ a^2) + SQRT[(1 + 0.25/ a^2)^2 - 1] or (1 + 0.25/ a^2) - SQRT[(1 + 0.25/ a^2)^2 - 1]

Compute using Excel can be obvious that only (a, a) = (-1, -1) or (1, 1) gives x = 2 or 0.5 to satisfy.

x^2 - (5/2) x + 1 = 0 is the only equation satisfies stated conditions.

Sum of all distinct x = 5/2 and therefore 5 + 2 = 7.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...